Association of cervical vertrebra anomalies with cleft lip and palate - Srivastava, Mudita; Aggarwal, Anshul; Batra, Puneet; Datana, Sangeev; Kumar, Prasanna; Macrcusson, KlaraAgneta (Journal of cleft lip palate and craniofacial anomalies, 2014)
Introduction: The aim of the present study was to evaluate the developmental relationship in the vertebral column in the cervical region and to relate its association in patient′s with cleft lip and palate. Materials and Methods: The sample consisted of 228 cleft patients in the experimental group and 225 non cleft samples in control group. Cleft patients are subdivided into cleft palate only (CPO), Unilateral cleft lip and palate (UCLP) and bilateral cleft lip and palate (BCLP). Cervical vertebrae were traced on lateral cephalogram in children with cleft lip and palate to determine the prevalence of vertebral anomalies and their categorization. The cervical vertebral anomalies were classified into two types: posterior arch deficiency (PAD) and fusion anomalies (FUS). Results and Conclusion: The study showed 19 percent of cleft patients with cervical vertebral anomalies and 4 percent of control group with cervical vertebral anomalies. Posterior arch deficiency occurred more frequently in unilateral cleft lip and palate(UCLP) and cleft palate only (CPO), Fusion occurred significantly more often in bilateral cleft lip and palate (BCLP).